Treatment of textile dye wastewaters using ferrous sulphate in a chemical coagulation/flocculation process - Carmen S. D. Rodrigues (2013)
The coagulation/flocculation treatment using FeSO4 center dot 7H(2)O as a coagulant is evaluated in this work for the removal of organic compounds and colour from synthetic effluents simulating the cotton, acrylic and polyester dyeing wastewaters. The coagulant dose, temperature, pH, stirring speed and stirring time that maximized the removal of dissolved organic carbon (DOC) and colour for each effluent are determined for the coagulation process. The effect of the stirring speed, stirring time and the dose of flocculant (Magnafloc 155 or Superfloc C-573) on the flocculation stage is also evaluated for effluents pretreated by coagulation at the optimal conditions previously determined. The obtained results showed that the optimal operating conditions are different for each effluent, and the process (coagulation/flocculation) as a whole was efficient in terms of colour removal (approximate to 91% for cotton, approximate to 94% for acrylic effluents; polyester effluent is practically colourless). However, the DOC removal observed is not significant (approximate to 33% for polyester, approximate to 45% for cotton and approximate to 28% for acrylic effluents). On the other hand, the remaining dissolved iron content is appropriate for further integrating the treatment with an iron-catalysed Fenton process, thus reducing the consumption of chemicals in the overall treatment.